Mengikis Ketergantungan: Dampak Program Pemberdayaan Terhadap Kehidupan Sosial Ekonomi Masyarakat Desa Sungai Pasir Kabupaten Sukamara - Rifanny, Muhammad Rizky; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2024)
The life of the fishing community in Sungai Pasir Village depends on the Fisherman Boss (Juragan Kampung), which makes the fishing community unable to live independently, until an empowerment programme through Vaname Shrimp farming for fishing communities in Sungai Pasir Village emerged. This research aims to analyse the community empowerment approach applied and the impact of the empowerment programme through vaname shrimp farming on the socio-economic life of the Sungai Pasir Village community. The theory used in this research is the theory of community empowerment (Jim lfe). The research approach used is qualitative, with a case study research type. Data collection used participant observation, in-depth interviews and documentation. Data was analysed using data reduction, data presentation and conclusion drawing. The results show that the vaname shrimp empowerment programme in Sungai Pasir Village has an impact on the socio-economic life of the community. The impacts are: the opening of employment opportunities for the community; a change in the profession of the community from fishermen to pond farmers; the emergence of community independence; increased community awareness to save; and, the birth of small micro businesses. The community conducts vaname shrimp farming activities in groups of 25 members. The group is called